Assessment of viability of microorganisms employing fluorescence techniques - Breeuwer, Pieter (Landbouwuniversiteit te Wageningen, 1996)
In conclusion, fluorescence techniques offer the possibility to study viability of a cell population employing microscopy, flow cytometry and image analysis. This may contribute to a better understanding of the mechanisms involved in selective survival of microorganisms under different stress conditions.